Soil phosphorus extracted by Bray 1 and Mehlich 3 soil tests as affected by the soil/solution ratio in Mollisols - Gutiérrez Boem, Flavio Hernán (2011)
Different relationships between soil-test methods results have been reported in several agricultural regions. Differences in the same soil-test procedure (e.g., soil/solution ratio) exist between soil-testing laboratories from different agricultural regions. Our objectives were to (1) determine the effect of soil/solution ratio on the amount of phosphorus removed by Bray 1 and Mehlich 3 methods, (2) compare the amounts of phosphorus removed by Bray 1 and Mehlich 3 in Mollisols from the Pampean region, and (3) determine whether soil/solution ratio affects the relationship between Bray 1 and Mehlich 3. Soil phosphorus availability was determined with two extractants (Bray 1 and Mehlich 3), using two soil/solution ratios (1:10 and 1:8, wt/v) in 72 soils (noncalcareous, loess-derived Molisolls) from the Pampean region. The amount of phosphorus removed was 20-24% greater when using 1:10 than 1:8 (wt/v) soil/solution ratio. This effect was significantly greater in Bray 1 than in Mehlich 3 (p = 0.04). When compared using the same soil/solution ratio, Mehlich 3 removed 4 to 8% more phosphorus than Bray 1. The soil/solution ratio used in the comparison affected the relationship between both extractants. The difference between extractants was slightly greater with a soil/solution ratio of 1:8 than of 1:10 (p = 0.03). Our results showed that even when using the same method, changes in the procedure (like soil/solution ratio) may cause different soil-test results and also differences in the relationship between two extracting solutions. Therefore, reported relationships between two methods are only valid for the soils and region where the relationship was developed and should not be extrapolated to other regions, even with similar soils. © Taylor & Francis Group, LLC.